To solve the equation 7x + 6y = -2 for y, we need to isolate y on one side of the equation.
Step 1: Start by subtracting 7x from both sides of the equation:
7x + 6y - 7x = -2 - 7x
Simplifying the left side gives us:
6y = -2 - 7x
Step 2: Now, let's isolate y by dividing both sides of the equation by 6:
6y/6 = (-2 - 7x)/6
Simplifying further, we get:
y = (-2 - 7x)/6
Therefore, the solution to the equation 7x + 6y = -2, when solved for y, is y = (-2 - 7x)/6.
Let's consider an example:
If x = 2, we can substitute this value into the equation to find y:
7(2) + 6y = -2
Simplifying:
14 + 6y = -2
Next, let's isolate y:
6y = -2 - 14
6y = -16
Dividing both sides by 6, we get:
y = -16/6
y = -8/3
So, when x = 2, the solution to the equation is y = -8/3.Answer:
Step-by-step explanation: